Barriers and facilitators of older people’s mHealth usage: A qualitative review of older people’s views - Spann, Alice; Stewart, Ellen (Human Technology, 2018)
The aim of this qualitative evidence synthesis is to identify and assess existing evidence on barriers to and facilitators of older people’s usage of mHealth. Existing literature identified many factors that affect people’s experiences and perceptions of mHealth, which are in turn influenced by their personal circumstances and biography. The following themes were identified using the thematic synthesis approach: (a) perception of usefulness, (b) user requirements, (c) self-efficacy, (d) sense of self and control, (e) privacy and confidentiality, and (f) cost. MHealth devices and services are complex interventions that have to be integrated into an older person’s life in order to facilitate effective use. Developers, providers, and policymakers should make sure that older people are included in decisions about technology use and, further, should question whether the current promotion of technology as a panacea for societal and budgetary problems is rooted in a realistic assessment of their use in practice.